The Evolution of Diversity Climate Research: A Review and Synthesis - Hazal Koray Alay; Esin Can (Istanbul Business Research (IBR), 2020)
The purpose of this paper is to integrate the results obtained from various studies on the diversity climate.The academic development of the concept of diversity climate in work life has been analyzed in a comprehensive way. Forty-one empirical studies published between 1975 and 2018 were retrieved from the ISI Web of Knowledge database and included in this theory-driven review. The main research questions of the current study are the following: “What do we know about the diversity climate in organizations? What theories is diversity climate based on? What is the focal point of the diversity climate? What are the dimensions and outcomes of diversity climate?”. The result suggests that the holistic picture about the diversity climate theories, variables, research method, unit of analysis and results of the articles reviewed.This research helps to identify diversity climate which is important for the graduate students, researchers and scholars who are interested or working in the field of diversity and diversity climate..
Keywords: 650; Diversity climate at workplace; Demographic minorities; Identity structure; Theory-driven review; Synthesiss